LARGE EDDY SIMULATION OF PARTIALLY PREMIXED O\TEXTSUBSCRIPT{2}-H\TEXTSUBSCRIPT{2} COMBUSTION WITH STEAM DILUTION IN MULTI-CLUSTER JET - Maruli Tondi, Gabriele
Over the past 150 years, carbon dioxide levels in the atmosphere have risen significantly, leading to rising temperatures in the atmosphere due to a perturbation of the natural carbon cycle. One proposed solution to this problem is using non-carbon fuels, such as hydrogen. Although hydrogen has a larger low heating value on a mass basis, it has a higher flame temperature, and is more flammable. These differences make it important to modify the current gas turbine systems. To address these challenges, a non-premixed multi-cluster jet configuration with steam dilution has been suggested. By using this configuration, the lifted flame is expected to be produced. In this study, large eddy simulation (LES) of oxy-hydrogen combustion with steam dilution will be conducted. LES is chosen due to its high fidelity and capability to provide an accurate turbulent structure. In the present study, the flow, flame structure, and behaviors produced during the combustion process will be analyzed. Furthermore, the effect of oxidizer jets’ angle and fuel jet velocity will also be studied. Three simulations with different oxidizers' jet angles and five variations of fuel jet velocity is done. In all cases, the oxidizers and fuel jets impinge on each other and repel hydrogen to the y-direction, produces the circulation flow, large vortical structures, and high-temperature regions around the inlet patch. It has also been found that non-premixed rich combustion dominate with triple flame is found. Comparison between the oxidizers’ jet angle cases has found that narrower and higher stoichiometric mixture fraction surface is produced in the bigger oxidizers’ jet angle, resulting in the domination of rich regions as the jet angle becomes larger. Larger oxidizer jets’ angle has also been found to yield less turbulence flow and more stable flame. Unlike the oxidizers’ jet angle cases, in the fuel jet velocity cases, a more stable flame is produced when turbulence becomes more intense. The maximum heat release rate is found about 270 W and 250 W in angle and fuel jet velocity cases, respectively.